Effects of agricultural credit facility on the agricultural production and rural development - Ekwere, GE; Edem, ID (International Journal of Environment, 2014)
Lack of capital has been identified as one of the constraints that faced by small scale farmers. The aim of this research was to examine the effect of agricultural credit on the agriculture production, and calculate the inputs and outputs among small scale farmers. Structured questionnaires were distributed to 136 farmers, who had been selected using the stratified random sampling technique, and the data obtained were summarized into percentages. Regression analysis was adopted to assess the impacts of socio-economic factors on loan size among farmers, while Cobb-Douglas Production Function Analysis (CDPFA) was used to test the relationship between key independent variables such as loan amount, farm size, inputs and farm output as dependent variable. The analysis revealed a significantly high value of coefficient of determination (R2= 0.922) that reflected a high relationship between the dependent variable and the independent variables; gender, age, education, family size, farm size, farming experience. The Adjusted (R2) coefficient (R2 = 0.918) revealed that 91.8 % of variation in loam size explained by the changes in variables. The results showed a significance in F-test in size of loan. The hypothesis two, exhibited that the independent variables; loan size, farm size, and inputs explained the variation in the total value of farmers output. The study therefore showed that to achieve the positive agricultural credit impacts on agricultural production, The Government and the private sector should regularly and timely facilitate the credit to the small scale farmers. DOI: http://dx.doi.org/10.3126/ije.v3i2.10529 International Journal of the Environment Vol.3(2) 2014: 192-204